The Influence of Quality, Price, and Promotion on Interest in Buying PT Sig Precision Interlock Brick Products in Java - Sofiyan Arif; Tongam Sirait (Green Publisher Indonesia, 2025)
This study is motivated by the need for effective marketing strategies to boost purchase intention of innovative products in the construction industry. The literature review discusses theories of consumer behavior, marketing mix, and empirical findings on the effects of quality, price, and promotion on purchase decisions, supported by works from Kotler & Keller, Hair et al., and recent scholars such as Azizah & Prasetya (2023) and Setiawan & Sunaryo (2024). The research employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM), with data collected through questionnaires from 100 users of interlock bricks in Java. The results indicate that all three independent variables quality, price, and promotion have a positive and significant effect on purchase intention, with an R-square value of 0.716. Product quality emerged as the dominant influence, followed by price and promotion. Validity and reliability tests confirm that all indicators meet the required thresholds. The study concludes that simultaneous efforts to enhance product quality, adjust pricing strategies, and implement educational promotions can effectively increase consumers’ purchase intention toward PT SIG’s precision interlock brick products.